Ethos of Librarians in Academic Libraries in Uganda: A Study of Unethical Practices - Nabbosa, Mary Gorreti; Kaddu , Sarah; Ssekitto, Francis (University of Dar es Salaam Library Journal, 2025)
This paper analyses the ethical practices of Ugandan academic librarians by studying student service experiences at Kyambogo University (KyU) and Uganda Christian University (UCU). Through focus group discussions conducted with twenty-three (23) Library and Information Science (LIS) students (n=14 Kyambogo; n=9 UCU) who served as participants sampled by convenience and purposive strategies, the study analysed the multifaceted aspects related to ethical conduct. The research revealed that students’ perceived expectations of research assistance, ICT, and reference services differed substantially from actual practice. Current unethical conduct includes librarian absence and book restrictions, as well as resource misuse. This ethical deficit arises from three main factors: insufficient, enforceable ethical standards at the national level, inadequate professional oversight systems, and cultural norms within UCU, exemplifying faith-based higher education that sometimes conceals underlying ethical difficulties. This research develops an Ubuntu-based ethical system to supplement the IFLA Code of Ethics tailored to the Ugandan sociocultural setting. The study promotes LIS education that focuses on ethics, along with continuous professional development initiatives, and the development of a code of conduct between libraries and the delivery of psychosocial services to librarians. The study brings sophistication to African library ethics scholarship by supplying ethical recommendations tailored for academic institutions based upon empirical findings. https://dx.doi.org/10.4314/udslj.v20i1.4